2013
DOI: 10.4161/epi.27554
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer DNA methylation marker panel validated with high performance in Non-Hodgkin lymphoma

Abstract: Genes with altered DNA methylation can be used as biomarkers for cancer detection and assessment of prognosis. Here we analyzed the methylation status of a colorectal cancer biomarker panel (CNRIP1, FBN1, INA, MAL, SNCA, and SPG20) in 97 cancer cell lines, derived from 17 different cancer types. Interestingly, the genes were frequently methylated also in hematological cancer types and were therefore subjected to analyses in primary tumor samples from the major types of non-Hodgkin lymphomas (NHL) and in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
1
25
0
1
Order By: Relevance
“…Previous studies have shown that expression of SNCA is regulated by hypermethylation of the CpG island in its promoter region in various human cancers . Demethylation drug treatment in MB cells showed reversed expression of this gene, suggesting that the silenced expression of SNCA might be due to epigenetic regulation, including DNA hypermethylation (Figure A).…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies have shown that expression of SNCA is regulated by hypermethylation of the CpG island in its promoter region in various human cancers . Demethylation drug treatment in MB cells showed reversed expression of this gene, suggesting that the silenced expression of SNCA might be due to epigenetic regulation, including DNA hypermethylation (Figure A).…”
Section: Resultsmentioning
confidence: 83%
“…3b). It is noteworthy that the CNRIP1 gene, which encodes a protein that interacts with the C-terminal tail of cannabinoid receptor 1, has been found to be frequently methylated in hematological cancer types (Bethge et al 2014). 3f; P = 0.78, Student's t-test).…”
Section: Validation Of Gene Methylation/hydroxymethylation By Qpcrmentioning
confidence: 99%
“…59665; Qiagen GmbH) as a negative control, unconverted human genomic DNA from healthy human blood samples, which was not amplified, and a no template control, including the entire ingredients of the reaction except the template DNA. The standard curve was plotted using the Cq value (13,14,18,19,34,37) of the methylated human bisulfite-converted DNA at various concentrations vs. the log value of input DNA concentration. An acceptable MethyLight PCR result was obtained, and is demonstrated by the PCR efficiency (96-102%), correct slope value (-3.65 --3.2) and R 2 =0.9985.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was reported that no significant difference was identified in the methylation status of these genes with clinicopathological characteristics of patients with CRC (17). Bethge et al (19) assessed CNRIP1, FBN1, INA, MAL, SNCA and SPG20 genes in 97 cancer cell lines, demonstrating that SNCA and SPG20 were methylated in 97 and 92% of the tumor samples, respectively. In the present study, it was demonstrated that SPG20 methylation exhibited a significantly higher sensitivity (81.1%) compared with the CEA tumor marker (48.6%).…”
Section: Hypermethylation Status In Plasma --------------------------mentioning
confidence: 99%
See 1 more Smart Citation